Diversifikasi dan Pengembangan Produk Hasil Samping Industri Rajungan: Pemberdayaan Masyarakat Mini Plant di Kabupaten Pemalang Jawa Tengah - Wini Trilaksani; Bambang Bambang; Wahyu Ramadhan; Joko Santoso; Zacky Ariviaie Santosa (Institut Pertanian Bogor, 2024)
The crab canning industry in Pemalang Regency has been built for over three decades and has become the largest in Indonesia, with 13 mini-plant units. Boiling and stripping are the main activities that produce a large amount of waste, causing pollution. The crab waste currently utilized by the local community as animal feed. Therefore, disseminating knowledge and skills regarding diversification and product development is necessary. The training aimed to deliver knowledge and skills concerning diversification and development of products for the mini-plant in Pemalang. Training consists of pre-activities, delivery of innovative content, development of various by-products, and evaluation. The innovative topic includes handling and potential use as instant food, snacks, seasoning, nova ingredients, and other non-food products. Diversification includes the innovation of traditional community-based products (tempe rajungan (teraja) and abon vegetable rajungan anaraja), innovation of regionally processed products (